2015
DOI: 10.1002/2015gl064424
|View full text |Cite
|
Sign up to set email alerts
|

Significant modulation of variability and projected change in California winter precipitation by extratropical cyclone activity

Abstract: Extratropical cyclones give rise to much of the precipitation over California. Observed California winter precipitation is highly correlated to a metric of extratropical cyclone activity over the Eastern Pacific. The lack of precipitation over the recent winters is coincident with consecutive winters of much below average cyclone activity. Analysis of variability in cyclone activity and California precipitation simulated by models participating in Coupled Model Intercomparison Project Phase 5 indicates that mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
68
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 29 publications
7
68
0
Order By: Relevance
“…The strong positive height anomaly strengthens the climatological mean ridge (Fig. 8a), which reduces the likelihood of winter storms reaching and affecting California, and deflects them toward the north and south (Wang et al 2014;Chang et al 2015). This can be seen in the composite of total cloud fraction anomaly in which large positive cloud fraction anomalies are located over western Canada and Mexico, while negative water vapor mixing ratio and total cloud fraction anomalies are located over California (Figs.…”
Section: Atmospheric Processes For Linkages Between Climate Indicementioning
confidence: 75%
“…The strong positive height anomaly strengthens the climatological mean ridge (Fig. 8a), which reduces the likelihood of winter storms reaching and affecting California, and deflects them toward the north and south (Wang et al 2014;Chang et al 2015). This can be seen in the composite of total cloud fraction anomaly in which large positive cloud fraction anomalies are located over western Canada and Mexico, while negative water vapor mixing ratio and total cloud fraction anomalies are located over California (Figs.…”
Section: Atmospheric Processes For Linkages Between Climate Indicementioning
confidence: 75%
“…Diffenbaugh et al [29•] examined the recent California drought and showed that whilst there was no apparent change in observed precipitation, the systematic warming over the past century meant that dry years were now almost invariably also warm years (hence increasing the proclivity of drought), whereas in the past, the combination of the two conditions was less common. California precipitation is controlled by dynamical processes related to the storm track, and its future evolution is therefore highly uncertain [30]. Without a clear prediction of precipitation changes, [29•] argue that the risk of drought in California is increasing.…”
Section: Dynamic and Thermodynamic Mechanismsmentioning
confidence: 99%
“…To explore a plausible, large-scale, physical mechanism favoring precipitation-phase changes between snow and rain, we performed single-point correlations [16] to calculate Pearson's correlation coefficient (r) between each SST grid point (averaged over winter) and the time series of the nine-station COOP median snow fractions from WY1951 to 2017. We removed linear trends from each time series prior to performing correlations [44].…”
Section: Large-scale Controls On Snow Level and Snow Fractionmentioning
confidence: 99%
“…The only significant negative correlations between snow fraction and SST anomalies (R 2 > 0.25, p < 0.05) were found immediately offshore of California. Following [16], we produced a time series by averaging SST anomalies in this region for comparison against snow-fraction anomalies. The resulting time series illustrates the generally negative correlation between SSTs and snow fractions (Figure 6b; note reversal of right y-axis) with occasional exceptions (e.g., WYs 1973 and 2013).…”
Section: Seasonal and Event Relationships Between Large-scale Circulamentioning
confidence: 99%
See 1 more Smart Citation